Oral milrinone for management of refractory right ventricular failure in patients with left ventricular assist devices. (29th July 2022) - Akhtar, Waqas; Butcher, Charles; Morley‐Smith, Andrew; Riesgo Gil, Fernando; Dar, Owais; Baston, Veronica; Dunning, John; Lyster, Haifa
Abstract: Aims: We present a single‐centre retrospective experience using oral milrinone in patients with a left ventricular assist device (LVAD) and concurrent refractory right ventricular failure. Methods and results: All patients implanted with LVAD between January 2013 and July 2021 from a high‐volume advanced heart failure service were reviewed. Eight patients were initiated on oral milrinone during this period. Oral milrinone was started 1.5 [inter‐quartile range (IQR) 1–2.3] years after LVAD implantation and continued for 1.2 (IQR 0.5–2.8) years. Therapeutic milrinone levels were achieved (232.2 ± 153.4 ng/mL) with 62.4 ± 18% of time within the therapeutic range. Two patients had adverse events (non‐sustained ventricular tachycardia and ventricular fibrillation effectively treated by internal cardioverter defibrillator) but did not require milrinone discontinuation. Four deaths occurred, one after transplant and three from disease progression determined to be unrelated to oral milrinone use. Three patients continue oral milrinone therapy in the community. There was no significant difference found after the initiation of oral milrinone on any of the physiological measures; however, there were trends in reduction of New York Heart Association class from 3.4 ± 0.5 to 3.0 ± 0.8 ( P  = 0.08), reduction of right atrial/wedge pressure from 0.9 ± 0.3 to 0.5 ± 0.2 ( P  = 0.08), and improvement of right ventricular stroke work index from 3.8 ± 2 to 5.8 ± 2.7 ( P  = 0.16). Conclusions: Oral milrinone appears safe for long‐term use in the outpatient setting when combined with therapeutic monitoring in this complex medical cohort with limited management options. Further study is needed to ascertain whether this treatment is effective in reducing heart failure symptoms and admissions.